What the New Testament authors really cared about : a survey of their writings - Berding, Kenneth; Williams, Matthew C (Grand Rapids, MI. Kregel Academic, 2015)
Fifteen top-rated professors from twelve leading Christian colleges and universities have collaborated to write this succinct, accessible New Testament survey
Includes bibliographical references and index
Keywords: Bible. -- Introductions